Residual ultimate strength assessment of double hull oil tanker after collision. (1st October 2017) - Parunov, Joško; Rudan, Smiljko; Bužančić Primorac, Branka
Highlights: Nonlinear finite element analysis of double hull oil tanker with side damage is performed. Systematic investigation of the influence of rotation of neutral axis is performed. Diagrams for rapid assessment of residual ultimate longitudinal strength are developed. Comparison with previous studies is performed. Abstract: The aim of the present study is the assessment of a residual ultimate strength of an Aframax-class double hull oil tanker damaged in collision. A contribution to the research of the problem is given in a systematic investigation of the influence of the rotation of neutral axis (NA), which is performed by imposing appropriate boundary conditions. Nonlinear finite element method (NFEM), using explicit dynamic integration method implemented in LS-Dyna, is employed. NFEM results are compared with the IACS CSR progressive collapse analysis (PCA) method. Residual strength diagrams are developed for a rapid residual ultimate longitudinal strength assessment in both sagging and hogging and accounting for correction factor because of the rotation of NA. Following this, developed diagrams are compared with previously published researches. The results of this study may be used by classification societies in a Rules development process, in the risk assessment studies of the maritime transportation and for a quick calculation of the hull girder residual strength of a damaged ship in the situation requiring emergency response action.